Using Database and Fuzzy Logic for Static and Dynamic Fitness Tests Representation - Abdullah, Omar Muayad; Ahmed, Esraa Khalid; Alkhayat, Rayan Yousif (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The fitness’s dynamic and static tests require the person being tested to run or walk as far as possible in a determined period, depending on some main factors it can be decide the status of the athletic. This work aims to create databases dedicated for dynamic and static fitness tests utilizing fuzzy logic to estimates athletic tests in different ages. The procedure of this work is divided into two steps, first determining the factors for processing, the second is the databases and FIS construction. The determined databases are considered as an inputs and output for proposed fuzzy logic system. There are two inputs (Age, Distance) and one output (Status), the membership functions for the first input (Age) are (Young Adults_A, Young Adults_B, Young Adults_C, Young Adults_D, Middle Aged_A, Middle Aged_B), the membership functions for the next input (Distance) are (Very Short, Short, Medium, Long, Very long), while the membership functions of the determined output (Status) are (Very Good, Good, Accepted, Bad, Very Bad). The procedure for creating proposed fuzzy logic structure is repeated twice, one for male and other for female.